Reducing the incidence and impact of peer-to-peer online trolling: a protocol for a scoping review - Daniel Johnson; Shasha Wang; Amanda Tracy Beatson; Aimee Riedel; Rory Mulcahy; Byron William Keating; Marilyn Campbell (BMJ Open, 2023)
Introduction Governments worldwide are committed to reducing the prevalence of peer-to-peer online trolling. The practice of peer-to-peer online trolling, which is broadly defined as where a user intends to cause disruption or conflict online for their own amusement or advantage, is a widespread pervasive and damaging behavior, affecting over one-third of all social media users. There remains, however, a substantial barrier to addressing this behaviour due to a lack of understanding of peer-to-peer online trolling and its unique psychopathology that distinguishes it from other forms of peer-to-peer online abuse such as cyberbullying and flaming, as well as the primary information technology approach used to investigate trolling. Providing a synthesis of peer-to-peer online trolling research will assist organisations, governments and educators in addressing this deviant behaviour online.Methods and analysis This protocol follows the six-stage scoping review process proposed by Arksey and O’Malley. Identifying the scoping review research question (stage 1) is followed by discussion on how studies will be selected (stage 2). We then discuss how we will determine which studies will be included in the scoping review (stage 3), as well as chart the data involved for each study included (stage 4). In stage 5, the scoping review protocol gathers, synthesises and reports the results, and consults with stakeholders about the initial protocol specifications (stage 6).Ethics and dissemination As the scoping review methodology focuses on incorporating information from available publications, ethical approval is not required. An article summarising the scoping review results will be submitted for publication to a journal, presented at appropriate conferences and disseminated as part of future workshops with professionals and educators involved in reducing online trolling.